Chaos from the ancient world to early modernity: formations of the formless - Höfele, Andreas; Levin, Christoph; Müller, Reinhard; Quiring, Björn (De Gruyter, 2021)
Frontmatter -- Table of Contents -- Image Credits -- Introduction -- The Invention of Chaos -- Zwischen Chaos und Ordnung -- Paradise Established -- Das umgestürzte Recht (Amos 5,7) -- Chaos in komischer Literatur des späten Mittelalters und der frühen Neuzeit -- Mixed Abysses -- “Come to Great Confusion” -- Sympathy Lost -- The Coming Chaos in Spenser and Milton -- The Tartarean Jurisdiction of Chaos in Milton’s Paradise Lost -- Naturalization of Chaos and Apotheosis of Order -- Index of Authors
Keywords: Aufsatzsammlung; Geschichte 1400-1700; Chaos; Literatur; Deutsch; Englisch; Schöpfung; Bibel / Altes Testament; Geschichte; Kosmogonie; Ordnung; Geistesgeschichte